Learners' perceptions of learners regarded as having a homosexual orientation in an independent secondary school environment - Hendrik P. Mostert; Chris Myburgh; Marie Poggenpoel (AOSIS, 2012)
In schools today discrimination based on sexual orientation takes place on a regular basis. This form of discrimination leads to aggression towards learners perceived to be homosexual, as well as towards those with a homosexual orientation. For more than 15 years South Africa has been a democratic country with laws that protect learners who have a homosexual orientation. Nevertheless, aggression and discrimination towards these learners still occur in schools. Aggression often leads to verbal and physical bullying of the victims by perpetrators. The objectives of this research were to explore and describe Grade 11 learners' experiences of aggression towards learners perceived to be homosexual as well as those with a homosexual orientation in an independent secondary school environment. The research design was qualitative, exploratory, descriptive and contextual in nature. The data for this investigation consisted of essays based on a published newspaper photograph, phenomenological group interviews, observations and field notes. Tesch's method of data analysis was used, and an independent coder assisted. Three themes were identified, discussed and supported by a literature control: that learners experience that it is right and acceptable to have a homosexual orientation; that they experience ambivalence towards homosexual orientation of learners; and experienced feelings that it is wrong to have a homosexual orientation. Recommended guidelines are provided to address aggression towards learners perceived to be homosexual and those with a homosexual orientation.